GATRA FISIOLOGIS DAN AGRONOMIS PADI DENGAN PENGAIRAN SISTEM GENANGAN DALAM PARIT DI INCEPTISOL - , Ir. Syamsuddin, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main staple food source of Indonesiaâs population is rice. Rice field require large amount of irrigation water. Rice is classified as plant with waste of water. The availability of water resource for irrigation has become limited. Research on âPhysiological and Agronomical Aspects of Rice under Saturated Soil Culture Irrigation System at Inceptisolâ was conducted in 3 stages of experiments. The first experiment was carried out to identified cultivar having good response to the satutrated soil culture (SSC) system and optimal bed width. The second experiment was to tudy the physiological and agronomical characters of cultivars having good response to SSC irrigation system and optimal planting distance. While for the third, the experiment was done to study water surface depth level in optimal furrow within each growth phase, irrigation water need, and its efficiency as well. The research was located at Sidoarum, district Godean, regency Sleman, Yogyakarta. It was held from April 2010 up to March 2012. Location of the study was region of rice field development with technical irrigation. The results showed that among 26 cultivars of rice, the âCimelatiâ was the most responsive cultivar and the âSarinahâ has less responsive. Potential yield of Cimelati and Sarinah were 25,02 and 21,46 g/plant. The optimal beds width was 4 m with furrow in both bed sides. Physiological and agronomical characters of rice showed the increasing values by SSC irrigation system comparing to the rice field involved leaf area index (LAI), chlorophyll content (a, b, total), prolin content, crop growth rate (CGR), dry shoot weight, maximum seed, productive seed and grain per plant. The decreased characters values involved stomata conductivity, transpiration rate, photosynthesis rate, net assimilation rate (NAR), relative growth rate (RGR), stomata opening width, relative water content (RWC), plant height, productive tiller percentage, panicle length, number of grain per panicle, grain content percentage and grain weight. While for non-changes characters, they involved lighting capture, leaf weight specific, leaf greenness, leaf stomata density, CO2 content of leaf cells, air temperature in leaf surface, leaf temperature and humidity, and grains weight per plant. Characters with largest contribution to the dry weight was CGR, 92,82% followed by transpiration rate 15.66%, proline content 11.15%, and leaf chlorophyll 9.66%. The optimal planting distance was 20 x 12,5 : 40 cm (as legowo). The water surface depth of furrow based on beds surface optimum for vegetative growth phase. In the generative phase required moisture levels higher than or close to field capacity moisture saturation levels. The optimal water surface depth of furrow based on beds surface was 0 cm at initial stage of growth (0 - 21 days after planting), and then 20 cm at active vegetative phase (21 - 60 days after planting), 0 cm for panicle initiation phase (61 - 90 days after planting), and 20 cm for flowering phase till full grain content (91 - 110 days) with 8,36 t/ha for un-hulled rice production. The need of irrigation water was 6.371 m3/ha/season, irrigation water reduction based on rice field technique was 47.39%, productivity of irrigation water was 1.31 g grain/kg of water, evapo-transpiration efficiency 3.41 g grain/kg water. The yield of rice with rice field technique was 8.59 t/ha.